Algeria : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2004)
Algeria remains heavily dependent on the hydrocarbon sector and still maintains a sizable and inefficient state-owned enterprise sector. Against this background, the paper addresses two different issues with important implications for macroeconomic stability in Algeria. The paper proposes the replacement of directed credit to large loss-making public enterprises with temporary and explicit budget subsidies. It also shows that money, volume of imports, and weather conditions have a strong impact on price movements in the short term, whereas the exchange rate has none.